Findings from the Evaluation of the WUN UK/Sino eChina Initiative - Dyke, Martin; Conole, Gráinne; Li, Zhen; Cai, Cynthia; Timmis, Sue (Proceedings of the International Conference on Networked Learning, 2006)
This paper presents the evaluation of a World Universities Network (WUN) eChina project: a Sino-UK collaborative e-learning initiative. The first phase of the project focused on module development, whilst the second phase focused on trialing and evaluation of these modules. The Universities of Bristol and Southampton carried out a needs analysis and evaluation of the 2005 trial in Northern China. Eighty-seven in-service teachers from six schools located in Beijing, Huairou and Shenyang participated. The paper provides feedback on the processes and experiences encountered in the project by both the development team and the participants involved in running and participating in the trial.